Refractory pseudomembranous colitis that was treated successfully with colonoscopic fecal microbial transplantation - Jun Young Shin; Eun Jung Ko; Seung Ho Lee; Jong Bum Shin; Shin Il Kim; Kye Sook Kwon; Hyung Gil Kim; Yong Woon Shin; Byoung Wook Bang (Intestinal Research, 2016)
Pseudomembranous colitis (PMC) is a nosocomial and opportunistic infection caused by Clostridium difficile. PMC is related to the use of antibiotics leading to intestinal dysbiosis and an overgrowth of C. difficile. Metronidazole or vancomycin is considered to be the standard therapy for the management of PMC. However, PMC has a 15%–30% recurrence rate and can be refractory to standard treatments, resulting in morbidity and mortality. Here we describe a patient who experienced refractory PMC who was treated with fecal microbiota transplantation. A 69-year-old woman was admitted to the hospital with consistent abdominal pain and diarrhea, which had been present for 5 months. She was diagnosed with PMC by colonoscopy and tested positive for C. difficile toxin. Even though she took metronidazole for 10 days, followed by vancomycin for 4 weeks, her symptoms did not improve. Because of her recurrent and refractory symptoms, we decided to perform fecal microbiota transplantation. Fifty grams of fresh feces from a donor were obtained on the day of the procedure, mixed with 500 mL of normal saline, and then filtered. The filtered solution was administered to the patient's colon using a colonoscope. After the procedure, her symptoms rapidly improved and a follow-up colonoscopy showed that the PMC had resolved without recurrence.